INNOVATIONS IN PEDAGOGICAL ACTIVITIES IN SCHOOLS OF LATVIA - Šteinberga, Airisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The topicality of the article is determined by the contradiction between the unequal speed of technology development and rigidity and conservatism of education system, which directly affects the pedagogical process and result, and which lags behind the development of society and technology. The consequences of this contradiction is the ever-increasing bureaucracy of the education system and the deterioration of the learning outcomes. In order to eliminate this contradiction, technological innovation is not enough. To reduce this contradiction, changes in the development of human mind, pedagogical activity and society as a whole, are necessary. The article analyses innovations in pedagogical activities – teachers’ mutual learning, model of pedagogical cooperation, study system at E.Blumss’ School and its organisation, concept of schools established by parent society and its implementation and introduction of these innovations in schools. For examples of implementation of pedagogical innovations are described, using the case study method to discover the efficiency of pedagogical innovations.